Fast assessing spalling risk of tunnel linings under RABT fire: From a coupled thermo-hydro-chemo-mechanical model towards an estimation method. (1st July 2017) - Zhang, Yiming; Zeiml, Matthias; Maier, Marcus; Yuan, Yong; Lackner, Roman
Highlights: An estimation method for assessing spalling risk of tunnel linings is presented. Method is built based on a coupled thermo-hydro-chemo-mechanical (THCM) model. Different concrete mixtures and moisture states are considered in the method. The estimation method is validated and calibrated with experimental observations. Abstract: Explosive spalling, i.e. the violent splitting of concrete pieces from the fire-loaded surface, greatly jeopardizes the integrity of tunnel structures. The assessment of the spalling risk of fire-loaded tunnel linings is an essential part of the design of new tunnels and the evaluation of the fire safety of existing tunnels. In this work, we present an estimation method capable of fast assessing the spalling risk of RABT 1 fire-loaded tunnel linings accounting for different concrete types and moisture contents. The estimation method is developed based on a well-established coupled thermo-hydro-chemo-mechanical (THCM) model. Furthermore, we also take advantage of the specific mechanic boundary conditions present in tunnel linings for simplifying the calculation model. Based on parameter studies covering a large range of concrete mixes and environmental conditions, empirical functions are developed to estimate the maximum pore pressure p max, all g and the so-called "required initial tensile strength" f t, 0 RE for quantifying the spalling risk. By comparing the results of f t, 0 RE with experimental observations such as the area of spalling, the proposed estimation method is calibrated and a general criterion is presented for assessing the spalling risk. Finally, as an illustrative example, the spalling risk of an Austrian highway tunnel built in the 1970s is assessed with the presented estimation method.